Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which of the given functions has a vertex at the origin, we need to analyze each function and identify its vertex.
### Function 1: [tex]\( f(x) = (x+4)^2 \)[/tex]
This function is a quadratic function in the standard form [tex]\((x-h)^2 + k\)[/tex], where the vertex is at [tex]\((h, k)\)[/tex]. Here, it can be rewritten as:
[tex]\[ f(x) = (x - (-4))^2 + 0 \][/tex]
This indicates that the function has a vertex at [tex]\((-4, 0)\)[/tex].
### Function 2: [tex]\( f(x) = x(x-4) \)[/tex]
To find the vertex of this quadratic function [tex]\( f(x) = x(x - 4) \)[/tex], we can rewrite it in the standard quadratic form [tex]\( ax^2 + bx + c \)[/tex]:
[tex]\[ f(x) = x^2 - 4x \][/tex]
The vertex of a quadratic function [tex]\( ax^2 + bx + c \)[/tex] is located at [tex]\( x = -\frac{b}{2a} \)[/tex]. Here, [tex]\( a = 1 \)[/tex] and [tex]\( b = -4 \)[/tex]:
[tex]\[ x = -\frac{-4}{2 \cdot 1} = 2 \][/tex]
Substituting [tex]\( x = 2 \)[/tex] back into the function to find the y-coordinate of the vertex:
[tex]\[ f(2) = 2(2 - 4) = 2(-2) = -4 \][/tex]
Thus, the vertex is at [tex]\((2, -4)\)[/tex].
### Function 3: [tex]\( f(x) = (x-4)(x+4) \)[/tex]
This function can be rewritten in the standard quadratic form:
[tex]\[ f(x) = x^2 - 16 \][/tex]
Using the vertex formula for [tex]\( ax^2 + bx + c \)[/tex], with [tex]\( a = 1 \)[/tex] and [tex]\( b = 0 \)[/tex], the vertex is:
[tex]\[ x = -\frac{b}{2a} = -\frac{0}{2 \cdot 1} = 0 \][/tex]
Substituting [tex]\( x = 0 \)[/tex] back into the function:
[tex]\[ f(0) = 0^2 - 16 = -16 \][/tex]
Thus, the vertex is at [tex]\((0, -16)\)[/tex].
### Function 4: [tex]\( f(x) = -x^2 \)[/tex]
This function is already in the standard quadratic form [tex]\(-x^2 + 0x + 0 \)[/tex], with [tex]\( a = -1 \)[/tex], [tex]\( b = 0 \)[/tex], and [tex]\( c = 0 \)[/tex]. The vertex formula [tex]\( x = -\frac{b}{2a} \)[/tex]:
[tex]\[ x = -\frac{0}{2 \cdot -1} = 0 \][/tex]
Substituting [tex]\( x = 0 \)[/tex] back into the function:
[tex]\[ f(0) = -(0)^2 = 0 \][/tex]
Thus, the vertex is at [tex]\((0, 0)\)[/tex].
### Conclusion:
The function that has a vertex at the origin [tex]\((0, 0)\)[/tex] is:
[tex]\[ f(x) = -x^2 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{4} \][/tex]
### Function 1: [tex]\( f(x) = (x+4)^2 \)[/tex]
This function is a quadratic function in the standard form [tex]\((x-h)^2 + k\)[/tex], where the vertex is at [tex]\((h, k)\)[/tex]. Here, it can be rewritten as:
[tex]\[ f(x) = (x - (-4))^2 + 0 \][/tex]
This indicates that the function has a vertex at [tex]\((-4, 0)\)[/tex].
### Function 2: [tex]\( f(x) = x(x-4) \)[/tex]
To find the vertex of this quadratic function [tex]\( f(x) = x(x - 4) \)[/tex], we can rewrite it in the standard quadratic form [tex]\( ax^2 + bx + c \)[/tex]:
[tex]\[ f(x) = x^2 - 4x \][/tex]
The vertex of a quadratic function [tex]\( ax^2 + bx + c \)[/tex] is located at [tex]\( x = -\frac{b}{2a} \)[/tex]. Here, [tex]\( a = 1 \)[/tex] and [tex]\( b = -4 \)[/tex]:
[tex]\[ x = -\frac{-4}{2 \cdot 1} = 2 \][/tex]
Substituting [tex]\( x = 2 \)[/tex] back into the function to find the y-coordinate of the vertex:
[tex]\[ f(2) = 2(2 - 4) = 2(-2) = -4 \][/tex]
Thus, the vertex is at [tex]\((2, -4)\)[/tex].
### Function 3: [tex]\( f(x) = (x-4)(x+4) \)[/tex]
This function can be rewritten in the standard quadratic form:
[tex]\[ f(x) = x^2 - 16 \][/tex]
Using the vertex formula for [tex]\( ax^2 + bx + c \)[/tex], with [tex]\( a = 1 \)[/tex] and [tex]\( b = 0 \)[/tex], the vertex is:
[tex]\[ x = -\frac{b}{2a} = -\frac{0}{2 \cdot 1} = 0 \][/tex]
Substituting [tex]\( x = 0 \)[/tex] back into the function:
[tex]\[ f(0) = 0^2 - 16 = -16 \][/tex]
Thus, the vertex is at [tex]\((0, -16)\)[/tex].
### Function 4: [tex]\( f(x) = -x^2 \)[/tex]
This function is already in the standard quadratic form [tex]\(-x^2 + 0x + 0 \)[/tex], with [tex]\( a = -1 \)[/tex], [tex]\( b = 0 \)[/tex], and [tex]\( c = 0 \)[/tex]. The vertex formula [tex]\( x = -\frac{b}{2a} \)[/tex]:
[tex]\[ x = -\frac{0}{2 \cdot -1} = 0 \][/tex]
Substituting [tex]\( x = 0 \)[/tex] back into the function:
[tex]\[ f(0) = -(0)^2 = 0 \][/tex]
Thus, the vertex is at [tex]\((0, 0)\)[/tex].
### Conclusion:
The function that has a vertex at the origin [tex]\((0, 0)\)[/tex] is:
[tex]\[ f(x) = -x^2 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{4} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.